2016
DOI: 10.1001/jamadermatol.2015.5944
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Application of Sunscreen Containing Titanium Dioxide Nanoparticles on Human Skin

Abstract: Services, nor does mention of trade names, commercial products, or organizations imply endorsement by the US government. This article reflects the views of the authors and should not be construed to represent FDA's views or policies. The mention of commercial products, their sources, or their use in connection with material reported herein is not to be construed as either an actual or implied endorsement of such products by the US Department of Health and Human Services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Under dark‐field microscopy, silver NPs were detected as orange spots in the dermis of skin samples treated with both 5 and 100 nm NPs at the third week in the dermal regions, mainly around the hair follicles (Figure B). A recent study describing the dermal penetration of TiO 2 NPs showed that NPs are detected in the dermis, surrounding the hair follicle, which was quite similar to our results. However, we assume that a small amount of NPs might penetrate the dermis and affect mast cells, because our in vitro results showed that a sub‐lethal dose of silver NPs could activate mast cells.…”
Section: Resultssupporting
confidence: 92%
“…Under dark‐field microscopy, silver NPs were detected as orange spots in the dermis of skin samples treated with both 5 and 100 nm NPs at the third week in the dermal regions, mainly around the hair follicles (Figure B). A recent study describing the dermal penetration of TiO 2 NPs showed that NPs are detected in the dermis, surrounding the hair follicle, which was quite similar to our results. However, we assume that a small amount of NPs might penetrate the dermis and affect mast cells, because our in vitro results showed that a sub‐lethal dose of silver NPs could activate mast cells.…”
Section: Resultssupporting
confidence: 92%
“…The limited nano‐TiO 2 skin penetration to the stratum corneum has been mostly confirmed by the updated literature, including a more recent individual study performed both in vitro and in vivo in rats and studies reported by the Australian Therapeutic Goods Administration (TGA), a part of the government health department, in their updated scientific review report concerning the safety of TiO 2 and ZnO nanoparticles in sunscreens in 2016 . The three studies reported by the Australian TGA that were published after the SCCS opinion were performed in vitro or in vivo in humans . The study performed in vitro and one of the studies performed in vivo in six subjects confirmed the limited nano‐TiO 2 skin penetration, which was not associated with diffusion into viable cells.…”
Section: Absorption and Distributionmentioning
confidence: 75%
“…The three studies reported by the Australian TGA that were published after the SCCS opinion were performed in vitro or in vivo in humans . The study performed in vitro and one of the studies performed in vivo in six subjects confirmed the limited nano‐TiO 2 skin penetration, which was not associated with diffusion into viable cells. However, the other studies performed in vivo in humans, which assessed repeated nano‐TiO 2 dermal exposure in two subjects, did not confirm these results .…”
Section: Absorption and Distributionmentioning
confidence: 75%
“…In addition, the skin itself has an antioxidant mechanism that neutralizes the effects ROS . Current evidence suggests that the nanoparticles may lodge in hair follicles but do not penetrate into the dermis in an significant amount . At present, there is no evidence that there are any consequences on human health, although there are insufficient data on inflamed skin where the epidermal barrier function has been compromised.…”
Section: Photoprotection: Update On Current Issuesmentioning
confidence: 99%